STRATEGI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA SEMARANG DALAM PELAKSANAAN PROGRAM KARTU IDENTITAS ANAK (KIA) UNTUK MEWUJUDKAN TERTIB ADMINISTRASI KEPENDUDUKAN DI KOTA SEMARANG - Ulum, Muhammad Nirwansyah; Astrika, Lusia (Journal of Politic and Government Studies, 2019)
The Regulation of the Minister of the Interior Number 2 Year 2016 onChildren Identity Card was enacted as a form of government policies for children’s protection of their identity rights. To follow up this regulation, Semarang City government issued Regional Regulation of Semarang City Number 4 Year 2016 on the Implementation of the Population Administration. The purposes of this study are to find out how the implementation of this regulation of the minister of the interior about Children Identity Card (KIA) in Semarang City is and what efforts have been done to overcome every obstacles. The results showed that Semarang City governments will carry out this regulation of the minister of the interior about Children Identity Card (KIA) in 2017. The preparations the Semarang City governments do are to collect datas of children, to discuss the addition of KIA’s benefits with several stakeholders, to conduct a comparative study into areas that have already implemented KIA, and to disseminate about KIA and its basic regulations. However during preparations Semarang City governments experiencedsome constraints such as, obscurity in distribution of KIA form, limitations anddelays in budget provision, lack of competent human resources to operatePopulation Administration Information System (SIAK) and the lack of regulationimplementing the Regional Regulation Number 4 Year 2016 on the Implementationof the Population Administration. Therefore, Semarang City governments makeefforts such as, provision of KIA own forms, preparation of training SIAKoperation, and make the technical regulation of Regional Regulation Number 4 Year2016 on the Implementation of the Population Administration.Keywords : Children Identity Card (KIA), Semarang City